Economics of Efficiency in Vegetable Business System of Mahakoshal Region in Madhya Pradesh - Singh, Manoj Kumar (Indian Journal of Marketing, 2004)
India is the largest producer of vegetables in the world after China. In Indian condition, vegetables are consumed in the form of fresh as well as cooked form. These vegetables are also consumed in the preserved form. As per the socio-economic norms of the Indian society, the trey of meal is considered incomplete if, it does not contain the dishes made up of fresh, cooked or preserved vegetables. Looking at this fact, it may be considered that vegetables play an important role in the life system of the Indian society. In other words, we can say that vegetables are playing an important role in Indian food habitat as well as the socio-economic life of the society/country. This gains more weightage when it becomes the second largest vegetable producer economy in the world.Vegetable crops provide a better opportunity to farmers for diversification of their farming scenario. This sector performs like the other sectors of Agriculture business like livestock, fishery, poultry etc and helps in improving the productivity of the land by generating employment, improving socio-economic status of the farmers and overall providing nutritional security to the family members as well as other people. Vegetable crops are important human food at all levels of development. Their role in popular diet, especially where rice and curry or chili dishes predominate, may well be underestimated, even if they do not figure largely in recorded market supplies.